The handbook of Chinese linguistics - Huang, Cheng-Teh James; Li, Y. H. Audrey; Simpson, Andrew (Blackwell handbooks in linguistics, 2014)
"Offers a unique, comprehensive introduction to Chinese linguistics from the perspective of modern theoretical and formal linguistics"--